Effect of extrusion on phenolics from Jizi439 black wheat bran: The profile, structure, and bioactivities. (1st March 2023) - Chen, Xi; Tang, Wenshuai; Li, Xinyue; Zhuang, Kun; Lyu, Qingyun; Ding, Wenping
Abstract: The effect of extrusion on the profile, structure, and bioactivities of phenolics from Jizi439 black wheat bran was investigated in this study. Extrusion process was carried out at 110 °C, 25% feed water content and 140 rpm screw speed. Total phenolic contents (TPCs) together with the levels of ferulic acid, vanillin, and apigenin that analyzed by HPLC were drastically elevated by extrusion (p < 0.05). Their corresponding derivatives including vanillin 4 -O- β-D-glucoside, ferulic acid 4 -O- β-D-glucoside, apigenin-4'-(3 -O- ( p- (E)-coumaroyl)-β-d -glucopyranoside), etc. were identified by UPLC-QTOF-MS/MS for the first time in black wheat. Furthermore, antioxidant, anti-diabetic, as well as anti-cancer activities were compared before and after extrusion. Results showed that extrusion could significantly improve the antioxidant activity of the phenolic extracts (p < 0.05). Both α-amylase and α-glucosidase treated with extracted phenolics at 50–1000 μg/mL from extruded black wheat bran showed a dose-dependent increase in their inhibitory rations. Significantly higher amount of Caco-2 cells were arrested at S-phase (p < 0.05) that leading to a higher percentage of apoptotic cells (p < 0.01) in extruded bran. Taken together, our study elucidated the changes in the profile, structures, and bioactivities of Jizi439 black wheat bran phenolics by extrusion, suggesting an efficiency approach for obtaining functional phenolics from the wheat milling by-products to improve their comprehensive utilization in food industry. Graphical abstract: Image 1 Highlights: Ferulic acid, vanillin, and apigenin were elevated by 10-fold after extrusion. Some phenolic derivatives were identified by UPLC-TOF-MS/MS for the first time in Jizi439 wheat. Antioxidant and anti-cancer activities were significantly improved by extrusion.